HAND BIOMETRICS - A TOOL FOR GENDER & STATURE ESTIMATION (Journal of Forensic Medicine & Toxicology, 2014)
Hand prints are one of the common evidences left at crime scene. A study was conducted on 140 medical students with an aim to establish a correlation of hand biometric measurements like hand length, hand breadth, palm legth, palm bredath, hand index and palm index from hand prints with stature and gender of an individual. Results of the study shows that hand length, palm length, hand breadth and palm breadth shows significant correlation with stature and gender of an individual as well as they show sexual diamorphism. Palm index and hand index neither shows significant correlation nor sexual diamorphism. Present study may be helpful to establish that hand dimensions from hand prints can effectively predict the stature and sexual dimorphism of an individualHence, the use of these parameters has been advocated in the present study.
Keywords: Hand Prints; Hand Biometrrics; Stature; Gender